Readability Testing as a Tool to Assess the Understanding of Medical Terms Used in Package Leaflets - E. I. Morkovin; E. Yu. Sorokina; A. G. Solodovnikov; D. V. Kurkin; A. A. Selezneva; S. A. Leshkova; A. V. Zaborovsky (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. The information that is intended for a patient and included in the package leaflet for a medicinal product should ensure the effective and safe use of the medicinal product through appropriate explanations. However, the appropriate level of detail and the necessity of defining each medical term are not clear.AIM. This study aimed to test how respondents without medical education, potentially representative of the general patient population, understand medical terms randomly selected from approved package leaflets for medicinal products authorised in the Russian Federation, as well as to conduct a statistical analysis of the relationships between the respondents’ demographics and test results.MATERIALS AND METHODS. A Google Forms-based comprehension test evaluated the understanding of 11 random terms from approved package leaflets for medicinal products authorised in the Russian Federation. The statistical analysis of comprehension included data from 63 respondents. The study collected the respondents’ demographic characteristics, including their level of education and age.RESULTS. The respondents overestimated their comprehension of medical terms, giving incorrect definitions to some terms that they previously deemed to be comprehensible. Overall, the respondents provided correct definitions for less than 80% of the terms tested. The most comprehensible terms were “rhinitis” (66.07%), “angioedema” (28.57%), “exanthema” (25.00%), and “anuria” (25.00%). Those who had a higher education or worked with documents were more likely to define the terms correctly.CONCLUSIONS. Package leaflets containing medical terms, regardless of how frequently these terms are used outside of healthcare settings, should be designed taking into account the heterogeneity of the target audience due to, among other things, differences in education. The terms that cause the greatest difficulty in user testing should be further explained or replaced with more understandable synonyms.